Evaluation of brain plasticity in patients with hypoglossal-facial nerve transfer: analysis of 70 cases - RANC, Revista Argentina de Neurocirugia; Bourguet, Martín Emilio; Biancardi, Mauro; Badilla Campos, Tomás Alfonso; Minghinelli, Federico Eduardo; Iglesias, Brenda; Socolovsky, Mariano (Revista Argentina de Neurocirugía, 2024)
Background: brain plasticity is crucial for regaining independent volitional control of facial muscles following hypoglossal-facial (HF) anastomosis, ensuring that tongue movements do not induce synchronous facial movements. Objective: to evaluate brain plasticity using the Plasticity Grading Scale (PGS). Methods: seventy patients were evaluated after an HF anastomosis: 1) using the donor nerve program, i.e., moving the tongue, and 2) activating the mimic muscle, consciously avoiding the use of the donor nerve. A 4-point Plasticity Grading Scale (PGS) was used to assess voluntary control. Results: 29 achieved a PGS of 1; 37 a PGS of 2; 4 a PGS of 3, and none reached a PGS of 4. A significant negative relationship (p <0.01) was observed between age and brain plasticity, implying that older age is associated with lower plasticity. A significant positive relationship (p <0.05) was also found between the quality/frequency of motor rehabilitation and brain plasticity, suggesting that better rehabilitation is associated with greater plasticity. Conclusion: brain plasticity was evaluated in 70 patients’ post-HF anastomosis. Age was negatively correlated, and the quality/frequency of rehabilitation was positively correlated with brain plasticity. However, no patient achieved the plasticity necessary for complete and independent voluntary control.